Impact of Nontariff Measures on Border Crossing Time and Costs: The Case of Perishable Goods Trade in the Central Asia Regional Economic Cooperation Region - DOROTHEA M. RAMIZO; AKIKO TERADA-HAGIWARA (Asian Development Review)
This study examines the effects of at-the-border and behind-the-border measures on the intraregional perishable goods trade in the Central Asia Regional Economic Cooperation region by combining trade facilitation indicators at the bilateral product level with an extensive dataset of nontariff measures. By utilizing a Poisson pseudo-maximum likelihood estimation technique in a gravity model, this study shows no empirical evidence that the time and cost associated with clearing perishable products at border crossing points harm intraregional trade. However, behind-the-border measures assume a more significant role in facilitating or impeding the perishable goods trade. Therefore, our findings highlight the importance of enacting structural reforms in trade facilitation—such as enhancing the capabilities and capacities of sanitary and phytosanitary laboratories, aligning regulations with international standards, simplifying and harmonizing documentary requirements, streamlining border processes, and promoting collaboration among customs and other relevant agencies involved in the trade of perishable goods.